Attentional control underlies the perceptual load effect: Evidence from voxel-wise degree centrality and resting-state functional connectivity. (24th October 2017) - Yin, Shouhang; Liu, Lu; Tan, Jinfeng; Ding, Cody; Yao, Dezhong; Chen, Antao
Highlights: The degree centrality (DC) correlate of perceptual load effect (PLE) is tested. PLE is correlated with DC in right middle temporal visual area (MT). PLE is correlated with connections between MT and dorsal attention network nodes. The attentional control is implicated in the generalization of the PLE. Abstract: The fact that interference from peripheral distracting information can be reduced in high perceptual load tasks has been widely demonstrated in previous research. The modulation from the perceptual load is known as perceptual load effect (PLE). Previous functional magnetic resonance imaging (fMRI) studies on perceptual load have reported the brain areas implicated in attentional control. To date, the contribution of attentional control to PLE and the relationship between the organization of functional connectivity and PLE are still poorly understood. In the present study, we used resting-state fMRI to explore the association between the voxel-wise degree centrality (DC) and PLE in an individual differences design and further investigated the potential resting-state functional connectivity (RSFC) contributing to individual's PLE. DC-PLE correlation analysis revealed that PLE was positively associated with the right middle temporal visual area (MT)—one of dorsal attention network (DAN) nodes. Furthermore, the right MT functionally connected to the conventional DAN and the RSFCs between right MT and DAN nodes were also positively associated with individual difference in PLE. The results suggest an important role of attentional control in perceptual load tasks and provide novel insights into the understanding of the neural correlates underlying PLE.